Expression of IMPDH mRNA after Mycophenolate Administration in Male Volunteers. (30th June 2014) - Kim, Sollip; Lee, Woochang; Chun, Sail; Um, Tae Hyun; Min, Won-Ki
Abstract : Background . Mycophenolic acid (MPA) is the first-line antimetabolic immunosuppressants used in solid organ transplantation. Here, in vivo expressions of the pharmacodynamic marker IMPDH mRNA were analyzed to investigate its usefulness in assessing drug effects. Materials and Methods . Six healthy male volunteers who had the same genotype for genes known to be associated with drug metabolism and effects were selected to remove the confounding effect of these genotypes. Mycophenolate mofetil (MMF, 1 g) was administered once to each subject, and blood samples were collected with certain interval before and after MMF administration to measure lymphocyte expression levels of IMPDH1 and IMPDH2 mRNA. One week later, the experiment was repeated. Results . Whereas IMPDH1 mRNA expression was stable, IMPDH2 mRNA expression showed 2 peaks in the first week. Both IMPDH1 and IMPDH2 mRNA expression in the second week remarkably decreased from the first week. Conclusion . The temporary increase in IMPDH2 mRNA expression in the first week might be due to a reactive reaction against the plasma MPA concentration. In the second week, the intracellular guanosine monophosphate might be depleted, rendering IMPDH2 mRNA synthesis inactive. When MPA is regularly administered to reach a steady state, the IMPDH2 mRNA expression may be kept low and may effectively reflect biological responses regardless of drug intake.